Litigation in Argentina: challenging the tobacco industry - Flores, M. L. (2006)
OBJECTIVE: To evaluate the processes and outcomes of tobacco litigation in Argentina and to analyse the strategies of the tobacco industry to oppose litigation using tobacco industry documents. METHODS: A systematic search of tobacco industry documents on the internet dating from 1978 to 2002. Law library searches using Argentinean official and unofficial reports systems were combined with computerised online searches. RESULTS: There have been at least 15 failed litigation cases in Argentina and the tobacco industry presented a concerted defence in every claim regardless of cost. We categorised 11 cases as product liability and nicotine addiction, two as health care reimbursement, and two as criminal law and secondhand smoke. Industry strategies included hiring legal consultants from prestigious international and Argentinean law firms and developing litigation prevention programmes. Industry monitored legal academic meetings, controlled the development of new product liability legislation, obtained favourable opinions from experts, and closely observed the development of litigation in Argentina. CONCLUSION: The strategies used by the industry have been successful in preventing recovery for tobacco injuries through litigation. Argentinean health advocates and lawyers need to be aware of the roles and strategies of the tobacco industry in order to develop effective litigation in Argentina.